Electronic structure and hybridization of CaS by means of X‐ray absorption spectroscopy at Ca and S K‐edges. (26th December 2012) - Xu, Wei; Liu, Lijuan; Cui, Mingqi; Zheng, Lei; Hu, Yongfeng; Marcelli, Augusto; Wu, Ziyu
<x xml:space="preserve">Abstract</x> The cubic calcium sulfide (CaS) is a well known system and an attractive building block material for many luminescence technological applications. However, it is essential to achieve an accurate understanding of its electronic structure in order to engineer its band structure for optimized applications. Here a study of the electronic structure of CaS by means of X‐ray absorption spectroscopy performed at both Ca and S K‐edges, and calculations performed in the framework of the multiple‐scattering theory and of the finite difference method are presented. At the Ca K‐edge the presence of an anomalous d states feature is discussed while in the S K‐edge spectrum the presence of a pre‐edge shoulder owing to the hybridization among Ca d states and S p states is pointed out. Although the l‐projected density of states of CaS is in good agreement with previous first‐principles calculations, the standard muffin‐tin potential is inadequate to reproduce near‐edge structures at both Ca and S K‐edges in this system. Indeed, with its highly symmetric and less compact structure, CaS is characterized by a large set of collinear atomic configurations that pose severe constraints on the construction of the atomic potential. On the contrary, the finite‐difference method with no muffin‐tin approximation is more suitable for X‐ray absorption calculations in this system.